PROBLEMS AND PROSPECTS OF TRAINING FOREIGN STUDENTS IN HIGHER EDUCATION INSTITUTIONS OF UKRAINE - KRYCHKIVSKA, Oksana; ZVARYCH, Hanna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract. The article identifies the strengths and weaknesses of the opportunities and threats to the training of foreign students in higher education institutions of Ukraine. The aim of the study is to specify the problems (weaknesses and threats) and prospects (strengths and opportunities) of training foreign students in higher education institutions of Ukraine in view of the current stage of development of society. To achieve this goal, the following objectives were achieved, including analyzing the latest research related to the education of foreign students in Ukraine, identifying the weaknesses and strengths of the education of foreign students in Ukraine, outlining the prospects for improving the quality of education of foreign students in Ukraine, and describing the challenges faced by the Ukrainian education system today. The main research methods are a comparative analysis of scientific studies, literature review, observation, systematization and generalization. A comparative analysis of domestic and foreign research is used to determine the level of accessibility and quality of education for foreign students. The author analyzes the legal documents establishing the rights and guarantees related to the training of foreign students in Ukraine. In support of its assertions, the article relies on the analysis of statistical and secondary data provided by Ukrainian and foreign researchers. The study conducted a SWOT-analysis of the training of foreign students in higher education institutions of Ukraine. The study analyzed the literature sources related to the research topic. The analysis highlights the strengths and weaknesses, opportunities and threats to the development of foreign students' education in Ukrainian higher education institutions. In the future, further research is planned to investigate the implementation of the educational process in the context of training foreign students in higher education institutions.